Measurement of the flow harmonic correlations in pp, p plus Pb and low multiplicity Pb plus Pb collisions with the ATLAS detector at the LHC - Çetin, Serkant Ali (ELSEVIER, 2019)
Recent measurements of the correlations between flow harmonics obtained using four-particle symmetric cumulants and three-particle asymmetric cumulants with the ATLAS detector at the LHC are described. The data sets of pp, p+Pb and peripheral Pb+Pb collisions at various energies are analyzed, aiming to probe the long-range collective nature of multi-particle production in small systems. The sensitivity of the standard cumulant method to non-flow correlations is investigated by introducing the subevents method. A systematic reduction of non-flow effects is observed when using the two-subevent method. Further reduction is observed with the three-subevent method that is consistent with the results obtained with the four-subevent one. A negative correlation between v(2) and v(3) and a positive correlation between v(2) and v(4), for all studied collision systems and over full multiplicity range, is observed. The correlation strength computed as symmetric cumulants normalized by the < v(n)(2)> is similar for all collision systems and weakly depends on multiplicity. These measurements provide new evidence for long-range multi-particle collectivity in small collision systems and quantify the nature of its event-by-event fluctuations.
Keywords: QGP; heavy ion collisions; small systems; collectivity; symmetric cumulants; subevent cumulants